Invasion and current distribution of the octocoral Carijoa riisei (Duchassaing & Michelotti, 1860) in the Ecuadorian coast (Eastern Tropical Pacific) - Cárdenas-Calle, Maritza (2021)
Carijoa riisei is a snowflake coral that has aggressively spread across many coastal habitats in the Atlantic and Pacific oceans, threatening a number of tropical ecosystems worldwide, including coral reefs. The aim of this work was to evaluate the distribution and provide an estimation of abundance of the invasive octocoral C. riisei along the Ecuadorian coast, as well as the relationship between its abundance and different environmental variables. In a field survey, high abundances of C. riiseicolonies were reported growing over corals and sessile communities at 5 of 43 sampling sites. The areas with highest relative abundance were found in the Manabí province, at two sites in Jama: Bajo Londres (44.57% coverage) and Vaca Brava 1(20.25%). Results of ordination and grouping statistical analyses showed no significant differences between invaded and not invaded sites as regards community compositionor environmental characteristics, suggesting neither biotic nor abiotic factors could be limiting C. riisei dispersal along the Ecuadorian coast. Results from a bibliographic survey covering occurrence data up to 2020 were in accordance, showing that inthat period C. riisei became an established species to the Ecuadorian coast, being present in at least 22 of the 43 sites, including various sites in Marine Protected Areas. Based on these findings, recommendations are made to promote urgent monitoring programs to detect C. riisei in new areas along the coast of Ecuador andin the Galapagos Marine Reserve, in order to develop a mitigation program and to take actions to conserve the ecosystems affected by this invasion.